2012
DOI: 10.1088/1748-0221/7/03/c03007
|View full text |Cite
|
Sign up to set email alerts
|

Liquefied Noble Gas (LNG) detectors for detection of nuclear materials

Abstract: Liquefied-noble-gas (LNG) detectors offer, in principle, very good energy resolution for both neutrons and gamma rays, fast response time (hence high-count-rate capabilities), excellent discrimination between neutrons and gamma rays, and scalability to large volumes. They do, however, need cryogenics. LNG detectors in sizes of interest for fissionable material detection in cargo are reaching a certain level of maturity because of the ongoing extensive R&D effort in highenergy physics regarding their use in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Hence, doping of xenon appears to reduce fluctuation in detected photons. A previous study with this detector also observed resolution improvement to 3% from 5% σ at 662 keV when doping pure argon with about 2000 ppm xenon [7].…”
Section: Energy Resolutionsupporting
confidence: 52%
See 3 more Smart Citations
“…Hence, doping of xenon appears to reduce fluctuation in detected photons. A previous study with this detector also observed resolution improvement to 3% from 5% σ at 662 keV when doping pure argon with about 2000 ppm xenon [7].…”
Section: Energy Resolutionsupporting
confidence: 52%
“…Previous studies have shown that the addition to argon of a few parts per million of xenon results in improved PSD [1], better energy resolution [7], and faster decay time [20]. As show in Table I, pure argon produces a wavelength of 128 nm, with decay times of 7 ns and 1.6 µs.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Liquid xenon (LXe) detectors have found many applications based on their capability to provide both calorimetry and imaging of particle interactions. Particularly fruitful applications include dark matter [1,2,3,4] and lepton flavor violating [5] searches, neutrinoless double beta decay detectors [6], gamma-ray physics experiments [7], medical imaging [8], and neutron detection for Homeland Security [9].…”
Section: Introductionmentioning
confidence: 99%